Preparation method of methanol synthesis catalyst with super-large specific surface area and catalyst

By using large specific surface area silica gel and carbon nanotubes as support and additives, a methanol synthesis catalyst with a super-large specific surface area was prepared, which solved the problems of small specific surface area of ​​the catalyst and poor dispersion of active components, and significantly improved the activity and stability of the catalyst.

CN119897117APending Publication Date: 2025-04-29SICHUAN OLEFIN CATALYTIC MATERIALS CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510084350.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The existing methanol synthesis catalyst has a small specific surface area and poor dispersion of active components, resulting in a short catalyst life, a fast decrease in activity and poor thermal stability.

Method used

A large specific surface area silica gel was used as a support, and a methanol synthesis catalyst with an ultra-large specific surface area was prepared by dispersing the modified silica gel support and carbon nanotubes, combined with co-precipitation and aging treatment.

Benefits of technology

It improves the activity, heat resistance and catalytic properties of the catalyst, extends the life of the catalyst, and enhances its stability under high pressure and high temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005249678240000161
    Figure BDA0005249678240000161
  • Figure BDA0005249678240000171
    Figure BDA0005249678240000171
  • Figure BDA0005249678240000172
    Figure BDA0005249678240000172
Patent Text Reader

Abstract

The invention relates to the technical field of catalyst production, in particular to a preparation method of a methanol synthesis catalyst with an ultra-large specific surface area and the catalyst, and the preparation method comprises the following steps: S1, taking silica gel as a carrier, and modifying to obtain a modified silica gel carrier; s2, dispersing the modified silica gel carrier and carbon nanotubes in a solution, and adding a nitrate mixed solution into the turbid liquid; s3, adding a sodium carbonate solution, precipitating the active component through cocurrent flow coprecipitation, adsorbing the active component on the carrier, and aging at constant temperature after cocurrent flow coprecipitation; s4, filtering the aged suspension, washing Na < + > in a filter cake with deionized water, and controlling the content of sodium oxide to be less than or equal to 0.10%; and S5, modifying, drying and roasting the filter cake in the step (4), and tabletting to obtain the filter cake with the required specification and size. By adopting the modified silica gel as the carrier, the methanol synthesis catalyst with an ultra-large specific surface can be obtained, the active components are more uniformly distributed on the surface of the carrier, and the prepared catalyst is high in activity and strong in heat resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of catalyst production, and in particular to a preparation method of a methanol synthesis catalyst with an ultra-large specific surface area and a catalyst. Background Art

[0002] The industrial production of methanol mainly adopts the method of CO / CO2 catalytic hydrogenation. CO / CO2 and hydrogen react under the action of catalyst to produce methanol, and the key technology of methanol synthesis is methanol synthesis catalyst. By the end of 2023, the domestic methanol production capacity will reach 107 million tons, and the scale of a single methanol synthesis unit will reach 2.2 million tons / year. However, the domestic million-ton methanol synthesis unit basically adopts foreign Lurgi technology and Davy technology. Foreign companies transfer technology and bundle catalysts for sale. The domestic catalyst market of tens of thousands of cubic meters is mostly occupied by foreign companies such as Johnson Matthey in the UK, Topsoe in Denmark and Klein in Germany. China needs to spend a lot of money on imports every year, and there are also risks of long supply cycles and key technologies being controlled by others.

[0003] At present, the methanol industry mainly uses copper-based catalysts, which are mainly divided into Cu-Zn, Cu-Zn-Cr, Cu-Zn-Al, Cu-Zr and other types. Among them, Cu-Zn-Al and Cu-Zn-Zr catalysts have excellent performance and are the catalysts mainly used in contemporary methanol production technology. The type, promoter and preparation process of copper-based catalysts have a great influence on the methanol yield and are the key technology for synthesizing methanol. With the rapid development of the methanol industry, domestic universities and research institutions have also been conducting research on methanol catalysts. The improvement of copper-based catalysts is mainly carried out from the aspects of auxiliary agent selection, carrier type selection and modification, and morphology adjustment. For example, CN102000578A, CN101983765A and CN102302934A of Dalian University of Technology add MgO, SiO2 or SiO2+MgO, SiO2+TiO2 and other auxiliary agents on the basis of copper-zinc-aluminum catalysts. After adding auxiliary agents, the CO2 conversion rate, methanol selectivity and catalyst stability of copper-zinc-aluminum catalysts are improved. The catalyst in CN102716749A includes Cu, Zn, Al, Zr and Mg, and the additives Zr and Mg are introduced at the same time to improve the conversion rate and selectivity of methanol synthesis by co-hydrogenation of CO and CO2. The catalyst composition in CN104275185A includes Cu, CuO, ZnO and Al2O3, and may also contain other additives, such as one or more of MgO, BaO, La2O3, CeO2, Ga2O3 and ZrO2, and the conversion rate of CO2 and the selectivity of methanol are improved. In addition to the above-mentioned metal additive modification, it can also be modified by non-metallic additives, such as the catalyst in CN105772000A is composed of Cu, ZnO, Al2O3 and graphene oxide, and a copper-based methanol synthesis catalyst promoted by reduced graphene oxide is used, the catalyst activity is high and stable, the operating temperature is low, and the CO2 conversion rate and methanol yield are significantly improved. In addition, the catalytic performance can be improved by forming a core-shell structure or improving the catalyst morphology. For example, CN105170151A uses Cu as the core and mesoporous SiO2 as the shell material, which can increase the specific surface area of ​​the catalyst and the dispersion of copper.

[0004] Although domestic universities and research institutes have done a lot of work on methanol synthesis catalysts, and certain types of methanol catalysts have been mass-produced by domestic enterprises and applied to large methanol plants, compared with foreign catalysts, domestic catalysts still have problems such as small catalyst specific surface area and poor dispersion of active components, resulting in shortcomings such as short catalyst life, rapid activity decline and poor thermal stability. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a methanol synthesis catalyst with an ultra-large specific surface area and a catalyst, so as to solve the technical problems of small specific surface area of ​​the catalyst and poor dispersibility of active components in the prior art.

[0006] The invention discloses a method for preparing a methanol synthesis catalyst with an ultra-large specific surface area, comprising the following steps:

[0007] S1. Silica gel is used as a carrier, and modified silica gel carrier is obtained after modification;

[0008] S2. The modified silica gel carrier and the carbon nanotubes are dispersed in a solution, and then a nitrate mixed solution is added to the suspension;

[0009] S3. Then, sodium carbonate solution was added, and the active component was precipitated by co-precipitation and adsorbed on the carrier, and after co-precipitation, the mixture was aged at a constant temperature;

[0010] S4. The aged suspension was filtered and the filter cake was washed with deionized water to remove the Na + , control the sodium oxide content ≤ 0.10%;

[0011] S5. The filter cake in step (4) is modified, dried, calcined, and then pressed into tablets to the required size.

[0012] Furthermore, the silica gel has a specific surface area of ​​≥350m 2 / g, pore diameter is 3-10nm, and pore volume is ≥0.50ml / g.

[0013] Furthermore, in step S1, the pressure in the reactor is controlled at 0.1-1 MPa, usually a normal pressure device.

[0014] Furthermore, the modified silica gel carrier modification method is to immerse it in 0.5-1.5 mol / L zirconium nitrate solution for multiple times at below 80°C, and then dry it at 260-450°C for 2-12 hours, and the zirconium nitrate in the zirconium nitrate solution is adsorbed on the silica gel surface in the form of zirconium oxide.

[0015] Furthermore, the weight ratio of the silica gel to the zirconium nitrate solution is 1:3-10, and the weight ratio of the silica gel to zirconium (zirconium oxide) in the modified silica gel carrier is 1:0.08-0.65.

[0016] Furthermore, the weight ratio of the modified silica gel carrier to the carbon nanotubes is 15 to 35:1.

[0017] Furthermore, the nitrate mixed solution includes zinc nitrate, copper nitrate, magnesium nitrate and rare earth nitrate, and the weight ratio of the carrier before modification to the nitrate mixed solution is 1:1:10-30.

[0018] Furthermore, in the nitrate mixed solution, the concentration of copper nitrate is 0.5-3 mol / L, the concentration of zinc nitrate is 0.2-1.5 mol / L, the concentration of rare earth nitrate is 0.001-0.01 mol / L, and the concentration of magnesium nitrate is 0.5-2 mol / L. Furthermore, the rare earth element in the rare earth nitrate is Lu, La, Ce or Y.

[0019] Furthermore, the concentration of the sodium carbonate solution is 0.5 to 3.0 mol / L.

[0020] Furthermore, during the parallel co-precipitation, the temperature is controlled at 50-90° C. and the pH is controlled at 6.5-9.5.

[0021] Furthermore, the aging time is 2 to 24 hours.

[0022] Furthermore, the filter cake is modified by immersing it in a 0.05-0.8 mol / L potassium hydroxide solution.

[0023] Furthermore, the drying is performed at 100-160° C. for 2-8 hours.

[0024] Furthermore, the calcination is carried out at 320°C to 400°C for 2 to 10 hours.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] 1. Using large specific surface silica gel as the carrier, a methanol synthesis catalyst with an ultra-large specific surface can be obtained. The active components are more evenly distributed on the carrier surface, and the prepared catalyst has high activity and strong heat resistance;

[0027] 2. The carrier is modified by ZrO2, which has special structural defects and promotes the active component, reducing the reduction temperature of the active component CuO, thereby improving the catalytic performance of the catalyst;

[0028] 3. By adding additives such as magnesium oxide and rare earth oxides, the conversion rate and selectivity of CO / CO2 and hydrogen to produce methanol are improved;

[0029] 4. The addition of carbon nanotubes to the catalyst can significantly increase the specific surface area of ​​the catalyst, and also has good hydrogen overflow performance, adsorption activation performance and strong hydrophobicity, which is beneficial to the desorption of H2O, the product of CO / CO2 hydrogenation to methanol reaction, reduces the inhibitory effect of H2O, and improves the catalytic activity and stability of the catalyst;

[0030] 5. The catalyst prepared by the present invention has a specific surface area of ​​140 to 210 m 2 / g or more, the methanol space-time yield evaluated at 5MPa and 230℃ is higher than 1.5-2.0g / h·ml-1 . DETAILED DESCRIPTION

[0031] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention are clearly and completely described below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments.

[0032] Example 1

[0033] This embodiment discloses a method for preparing a methanol synthesis catalyst with an ultra-large specific surface area, comprising the following steps:

[0034] (1) This method uses a specific surface area of ​​360m 2 / g of silica gel as a carrier, it was supersaturated with 0.55mol / L zirconium nitrate solution 5 times its weight at 60℃, and then heated at 260℃

[0035] Bake for 8 hours, soak and dry again to prepare a modified silica gel carrier;

[0036] (2) The modified silica gel carrier and the carbon nanotubes are suspended in water, the weight ratio of the carrier to the carbon nanotubes is 20:1, and water 4 times the weight of the carrier is added to mix evenly, and a nitrate mixed solution of copper nitrate, zinc nitrate, magnesium nitrate and lanthanum nitrate is prepared with water 20 times the weight of the carrier, with concentrations of 1.9 mol / L, 0.6 mol / L, 0.8 mol / L and 0.025 mol / L, respectively, and then the nitrate mixed solution is mixed evenly with the suspension of the carrier and the carbon nanotubes;

[0037] (3) preparing a sodium carbonate solution with 4 times the weight of water of the mixed solution in step (2), wherein the concentration of the sodium carbonate solution is 0.8 mol / L, and then co-precipitating the prepared sodium carbonate solution with the mixed solution in step (2), stirring vigorously during mixing, controlling the pH of the mixed solution to 7.5 and the temperature to 80° C., and aging the mixed solution for 4 h after heat preservation;

[0038] (4) Filter the aged suspension in step (3), and wash the filter cake with deionized water until Na + The concentration is less than 0.1% (calculated as sodium oxide);

[0039] (5) adding 0.05 mol / L potassium hydroxide salt solution at a concentration of 8% by weight of the filter cake to the filter cake in step (4) and mixing well, drying the filter cake at 120° C. for 4 h, drying at 350° C. for 2 h, and then pressing the filter cake into a Φ5*5 mm shaped catalyst;

[0040] (6) The prepared methanol synthesis catalyst was subjected to component analysis and specific surface analysis, and then subjected to 5MPa, 230℃, 10000h -1Performance evaluation was performed under airspeed conditions.

[0041] Example 2

[0042] This embodiment discloses a method for preparing a methanol synthesis catalyst with an ultra-large specific surface area, comprising the following steps:

[0043] (1) This method uses a specific surface area of ​​360m 2 / g of silica gel as a carrier, it was supersaturated with 0.65mol / L zirconium nitrate solution 5 times its weight at 65℃, and then heated at 280℃

[0044] Bake for 6 hours, soak and dry again to prepare a modified silica gel carrier;

[0045] (2) The modified silica gel carrier and the carbon nanotubes are suspended in water, the weight ratio of the carrier to the carbon nanotubes is 20:1, and water 4 times the weight of the carrier is added to mix evenly, and a nitrate mixed solution of copper nitrate, zinc nitrate, magnesium nitrate, lanthanum nitrate and lutetium nitrate is prepared with water 20 times the weight of the carrier, with concentrations of 2.0 mol / L, 0.7 mol / L, 0.15 mol / L, 0.03 mol / L and 0.03 mol / L, respectively, and then the nitrate mixed solution is mixed evenly with the suspension of the carrier and the carbon nanotubes;

[0046] (3) preparing a sodium carbonate solution with 3 times the weight of water of the mixed solution in step (2), wherein the concentration of the sodium carbonate solution is 1.0 mol / L, and then co-precipitating the prepared sodium carbonate solution with the mixed solution in step (2), stirring vigorously during mixing, controlling the pH of the mixed solution to 8.2 and the temperature to 80° C., and aging the mixed solution for 6 hours after mixing;

[0047] (4) Filter the aged suspension in step (3), and wash the filter cake with deionized water until Na + The concentration is less than 0.1% (calculated as sodium oxide);

[0048] (5) adding 0.05 mol / L potassium hydroxide salt solution at a concentration of 8% by weight of the filter cake to the filter cake in step (4) and mixing well, drying the filter cake at 150° C. for 6 h and at 350° C. for 3 h, and then pressing the filter cake into a Φ5*5 mm shaped catalyst;

[0049] (6) The prepared methanol synthesis catalyst was subjected to component analysis and specific surface analysis, and then subjected to 5MPa, 230℃, 10000h -1 Performance evaluation was performed under airspeed conditions.

[0050] Example 3

[0051] This embodiment discloses a method for preparing a methanol synthesis catalyst with an ultra-large specific surface area, comprising the following steps:

[0052] (1) This method uses a specific surface area of ​​360m 2 / g of silica gel as a carrier, it was supersaturated with 1.60mol / L zirconium nitrate solution 5 times its weight at 65℃, and then heated at 420℃

[0053] Bake for 6 hours, and repeat the soaking and drying twice to prepare a modified silica gel carrier;

[0054] (2) The modified silica gel carrier and the carbon nanotubes are suspended in water, the weight ratio of the carrier to the carbon nanotubes is 25:1, and water 4 times the weight of the carrier is added to mix evenly, and a nitrate mixed solution of copper nitrate, zinc nitrate, magnesium nitrate, lanthanum nitrate and lutetium nitrate is prepared with water 20 times the weight of the carrier, with concentrations of 2.7 mol / L, 1.2 mol / L, 0.25 mol / L, 0.06 mol / L and 0.035 mol / L, respectively, and then the nitrate mixed solution is mixed evenly with the suspension of the carrier and the carbon nanotubes;

[0055] (3) preparing a sodium carbonate solution with 3 times the weight of water of the mixed solution in step (2), wherein the concentration of the sodium carbonate solution is 1.4 mol / L, and then co-precipitating the prepared sodium carbonate solution with the mixed solution in step (2), stirring vigorously during mixing, controlling the pH of the mixed solution to 7.3 and the temperature to 75° C., and aging the mixed solution for 6 hours after mixing;

[0056] (4) Filter the aged suspension in step (3), and wash the filter cake with deionized water until Na + The concentration is less than 0.1% (calculated as sodium oxide);

[0057] (5) adding 0.05 mol / L potassium hydroxide salt solution at a concentration of 12% by weight of the filter cake to the filter cake in step (4) and mixing well, drying the filter cake at 120° C. for 6 h, drying at 350° C. for 3 h, and then pressing the filter cake into a Φ5*5 mm shaped catalyst;

[0058] (6) The prepared methanol synthesis catalyst was subjected to component analysis and specific surface analysis, and then subjected to 5MPa, 230℃, 10000h -1 Performance evaluation was performed under airspeed conditions.

[0059] Example 4

[0060] This embodiment discloses a method for preparing a methanol synthesis catalyst with an ultra-large specific surface area, comprising the following steps:

[0061] (1) This method uses a specific surface area of ​​360m 2 / g of silica gel as a carrier, it was supersaturated with 1.70mol / L zirconium nitrate solution 5 times its weight at 75℃, and then heated at 420℃

[0062] Bake for 6 hours, and repeat the soaking and drying twice to prepare a modified silica gel carrier;

[0063] (2) The modified silica gel carrier and the carbon nanotubes are suspended in water, the weight ratio of the carrier to the carbon nanotubes is 25:1, and water 4 times the weight of the carrier is added to mix evenly, and a nitrate mixed solution of copper nitrate, zinc nitrate, magnesium nitrate, lanthanum nitrate and yttrium nitrate is prepared with water 20 times the weight of the carrier, with concentrations of 2.3 mol / L, 1.25 mol / L, 0.21 mol / L, 0.06 mol / L and 0.043 mol / L, respectively, and then the nitrate mixed solution is mixed evenly with the suspension of the carrier and the carbon nanotubes;

[0064] (3) preparing a sodium carbonate solution with 3 times the weight of water of the mixed solution in step (2), wherein the concentration of the sodium carbonate solution is 1.3 mol / L, and then co-precipitating the prepared sodium carbonate solution with the mixed solution in step (2), stirring vigorously during mixing, controlling the pH of the mixed solution to 7.3 and the temperature to 80° C., and aging the mixed solution for 5 h after heat preservation;

[0065] (4) Filter the aged suspension in step (3), and wash the filter cake with deionized water until Na + The concentration is less than 0.1% (calculated as sodium oxide);

[0066] (5) adding 0.05 mol / L potassium hydroxide salt solution at a concentration of 15% by weight of the filter cake to the filter cake in step (4) and mixing well, drying the filter cake at 120° C. for 6 h, drying at 350° C. for 3 h, and then pressing the filter cake into a Φ5*5 mm shaped catalyst;

[0067] (6) The prepared methanol synthesis catalyst was subjected to component analysis and specific surface analysis, and then subjected to 5MPa, 230℃, 10000h -1 Performance evaluation was performed under airspeed conditions.

[0068] Example 5

[0069] This embodiment discloses a method for preparing a methanol synthesis catalyst with an ultra-large specific surface area, comprising the following steps:

[0070] (1) This method uses a specific surface area of ​​360m 2 / g of silica gel as a carrier, it was supersaturated with 0.4mol / L zirconium nitrate solution 5 times its weight at 80℃, and then heated at 420℃

[0071] Bake for 6 hours, and repeat the soaking and drying once to prepare a modified silica gel carrier;

[0072] (2) The modified silica gel carrier and the carbon nanotubes are suspended in water, the weight ratio of the carrier to the carbon nanotubes is 25:1, 5 times the weight of the carrier is added with water and mixed evenly, and a nitrate mixed solution of copper nitrate, zinc nitrate, magnesium nitrate, lanthanum nitrate and yttrium nitrate is prepared with water 20 times the weight of the carrier, the concentrations of which are 2.2 mol / L, 1.25 mol / L, 0.016 mol / L, 0.012 mol / L and 0.063 mol / L, respectively, and then the nitrate mixed solution is mixed evenly with the suspension of the carrier and the carbon nanotubes;

[0073] (3) preparing a sodium carbonate solution with 3 times the weight of water of the mixed solution in step (2), wherein the concentration of the sodium carbonate solution is 1.15 mol / L, and then co-precipitating the prepared sodium carbonate solution with the mixed solution in step (2), stirring vigorously during mixing, controlling the pH of the mixed solution to 7.8 and the temperature to 80° C., and aging the mixed solution for 5 h after heat preservation;

[0074] (4) Filter the aged suspension in step (3), and wash the filter cake with deionized water until Na + The concentration is less than 0.1% (calculated as sodium oxide);

[0075] (5) adding 0.08 mol / L potassium hydroxide salt solution at a concentration of 10% by weight of the filter cake to the filter cake in step (4) and mixing well, drying the filter cake at 120° C. for 6 h and at 350° C. for 3 h, and then pressing the filter cake into a Φ5*5 mm shaped catalyst;

[0076] (6) The prepared methanol synthesis catalyst was subjected to component analysis and specific surface analysis, and then subjected to 5MPa, 230℃, 10000h -1 Performance evaluation was performed under airspeed conditions.

[0077] Example 6

[0078] This embodiment discloses a method for preparing a methanol synthesis catalyst with an ultra-large specific surface area, comprising the following steps:

[0079] (1) This method uses a specific surface area of ​​360m 2 / g silica gel was used as a carrier, and it was supersaturated with 0.8mol / L zirconium nitrate solution of 5 times its weight at 80℃, and then heated at 350℃

[0080] Bake for 8 hours, and repeat the soaking and drying once to prepare a modified silica gel carrier;

[0081] (2) The modified silica gel carrier and the carbon nanotubes are suspended in water, the weight ratio of the carrier to the carbon nanotubes is 25:1, 5 times the weight of the carrier is added with water and mixed evenly, and a nitrate mixed solution of copper nitrate, zinc nitrate, magnesium nitrate and lanthanum nitrate is prepared with water 20 times the weight of the carrier, the concentrations of which are 2.0 mol / L, 1.125 mol / L, 0.026 mol / L and 0.047 mol / L, respectively, and then the nitrate mixed solution is mixed evenly with the suspension of the carrier and the carbon nanotubes;

[0082] (3) preparing a sodium carbonate solution with 3 times the weight of water of the mixed solution in step (2), wherein the concentration of the sodium carbonate solution is 1.0 mol / L, and then co-precipitating the prepared sodium carbonate solution with the mixed solution in step (2), stirring vigorously during mixing, controlling the pH of the mixed solution to 7.5 and the temperature to 80° C., and aging the mixed solution for 5 h after heat preservation;

[0083] (4) Filter the aged suspension in step (3), and wash the filter cake with deionized water until Na + The concentration is less than 0.1% (calculated as sodium oxide);

[0084] (5) adding 0.08 mol / L potassium hydroxide salt solution at a concentration of 12% by weight of the filter cake to the filter cake in step (4) and mixing well, drying the filter cake at 120° C. for 6 h and at 300° C. for 8 h, and then pressing the filter cake into a Φ5*5 mm shaped catalyst;

[0085] (6) The prepared methanol synthesis catalyst was subjected to component analysis and specific surface analysis, and then subjected to 5MPa, 230℃, 10000h -1 Performance evaluation was performed under airspeed conditions.

[0086] Example 7

[0087] This embodiment discloses a method for preparing a methanol synthesis catalyst with an ultra-large specific surface area, comprising the following steps:

[0088] (1) This method uses a specific surface area of ​​360m 2 / g silica gel was used as a carrier, and it was supersaturated with 1.0 mol / L zirconium nitrate solution of 5 times its weight at 80°C, and then heated at 350°C.

[0089] Bake for 8 hours, and repeat the soaking and drying once to prepare a modified silica gel carrier;

[0090] (2) The modified silica gel carrier and the carbon nanotubes are suspended in water, the weight ratio of the carrier to the carbon nanotubes is 30:1, 5 times the weight of the carrier is added with water and mixed evenly, and a nitrate mixed solution of copper nitrate, zinc nitrate, magnesium nitrate and cerium nitrate is prepared with water 20 times the weight of the carrier, the concentrations of which are 1.95 mol / L, 0.9 mol / L, 0.043 mol / L and 0.031 mol / L, respectively, and then the nitrate mixed solution is mixed evenly with the suspension of the carrier and the carbon nanotubes;

[0091] (3) preparing a sodium carbonate solution with 3 times the weight of water of the mixed solution in step (2), wherein the concentration of the sodium carbonate solution is 1.0 mol / L, and then co-precipitating the prepared sodium carbonate solution with the mixed solution in step (2), stirring vigorously during mixing, controlling the pH of the mixed solution to 8.1 and the temperature to 80° C., and aging the mixed solution for 5 h after heat preservation;

[0092] (4) Filter the aged suspension in step (3), and wash the filter cake with deionized water until Na + The concentration is less than 0.1% (calculated as sodium oxide);

[0093] (5) adding 0.07 mol / L potassium hydroxide salt solution at a concentration of 15% by weight of the filter cake to the filter cake in step (4) and mixing well, drying the filter cake at 150° C. for 6 h and at 380° C. for 4 h, and then pressing the filter cake into a Φ5*5 mm shaped catalyst;

[0094] (6) The prepared methanol synthesis catalyst was subjected to component analysis and specific surface analysis, and then subjected to 5MPa, 230℃, 10000h -1 Performance evaluation was performed under airspeed conditions.

[0095] Example 8

[0096] This embodiment discloses a method for preparing a methanol synthesis catalyst with an ultra-large specific surface area, comprising the following steps:

[0097] (1) This method uses a specific surface area of ​​360m 2 / g silica gel was used as a carrier, and it was supersaturated with 1.5 mol / L zirconium nitrate solution of 5 times its weight at 80°C, and then heated at 400°C.

[0098] Bake for 10 hours, and repeat the soaking and drying once to prepare a modified silica gel carrier;

[0099] (2) The modified silica gel carrier and the carbon nanotubes are suspended in water, the weight ratio of the carrier to the carbon nanotubes is 30:1, 5 times the weight of the carrier is added with water and mixed evenly, and a nitrate mixed solution of copper nitrate, zinc nitrate, magnesium nitrate and cerium nitrate is prepared with water 20 times the weight of the carrier, the concentrations of which are 2.5 mol / L, 0.5 mol / L, 0.067 mol / L and 0.025 mol / L, respectively, and then the nitrate mixed solution is mixed evenly with the suspension of the carrier and the carbon nanotubes;

[0100] (3) preparing a sodium carbonate solution with 3 times the weight of water of the mixed solution in step (2), wherein the concentration of the sodium carbonate solution is 1.0 mol / L, and then co-precipitating the prepared sodium carbonate solution with the mixed solution in step (2), stirring vigorously during mixing, controlling the pH of the mixed solution to 7.2 and the temperature to 85° C., and aging the mixed solution for 10 h after heat preservation;

[0101] (4) Filter the aged suspension in step (3), and wash the filter cake with deionized water until Na + The concentration is less than 0.1% (calculated as sodium oxide);

[0102] (5) adding 0.08 mol / L potassium hydroxide salt solution at a concentration of 15% by weight of the filter cake to the filter cake in step (4) and mixing well, drying the filter cake at 130° C. for 8 h, drying at 380° C. for 4 h, and then pressing the filter cake into a Φ5*5 mm shaped catalyst;

[0103] (6) The prepared methanol synthesis catalyst was subjected to component analysis and specific surface analysis, and then subjected to 5MPa, 230℃, 10000h -1 Performance evaluation was performed under airspeed conditions.

[0104] Example 9

[0105] This embodiment discloses a method for preparing a methanol synthesis catalyst with an ultra-large specific surface area, comprising the following steps:

[0106] (1) This method uses a specific surface area of ​​360m 2 / g silica gel as the carrier, and supersaturated impregnation with 5 times the weight of 1.2mol / L zirconium nitrate solution at 80℃, and then at 400℃

[0107] Bake for 10 hours, and repeat the soaking and drying twice to prepare a modified silica gel carrier;

[0108] (2) The modified silica gel carrier and the carbon nanotubes are suspended in water, the weight ratio of the carrier to the carbon nanotubes is 20:1, 5 times the weight of the carrier is added with water and mixed evenly, and a nitrate mixed solution of copper nitrate, zinc nitrate, magnesium nitrate and cerium nitrate is prepared with water 15 times the weight of the carrier, the concentrations of which are 2.4 mol / L, 0.63 mol / L, 0.077 mol / L and 0.043 mol / L, respectively, and then the nitrate mixed solution is mixed evenly with the suspension of the carrier and the carbon nanotubes;

[0109] (3) preparing a sodium carbonate solution with 3 times the weight of water of the mixed solution in step (2), wherein the concentration of the sodium carbonate solution is 1.0 mol / L, and then co-precipitating the prepared sodium carbonate solution with the mixed solution in step (2), stirring vigorously during mixing, controlling the pH of the mixed solution to 7.4 and the temperature to 80° C., and aging the mixed solution for 10 h after heat preservation;

[0110] (4) Filter the aged suspension in step (3), and wash the filter cake with deionized water until Na + The concentration is less than 0.1% (calculated as sodium oxide);

[0111] (5) adding 0.1 mol / L potassium hydroxide salt solution at a concentration of 13% of the filter cake weight to the filter cake in step (4) and mixing evenly, drying the filter cake at 130° C. for 8 h, drying at 380° C. for 4 h, and then pressing the filter cake into a Φ5*5 mm shaped catalyst;

[0112] (6) The prepared methanol synthesis catalyst was subjected to component analysis and specific surface analysis, and then subjected to 5MPa, 230℃, 10000h -1 Performance evaluation was performed under airspeed conditions.

[0113] Example 10

[0114] This embodiment discloses a method for preparing a methanol synthesis catalyst with an ultra-large specific surface area, comprising the following steps:

[0115] (1) This method uses a specific surface area of ​​360m 2 / g silica gel was used as a carrier, and it was supersaturated with 1.25mol / L zirconium nitrate solution of 5 times its weight at 80℃, and then heated at 400℃

[0116] Bake for 10 hours, and repeat the soaking and drying twice to prepare a modified silica gel carrier;

[0117] (2) The modified silica gel carrier and the carbon nanotubes are suspended in water, the weight ratio of the carrier to the carbon nanotubes is 20:1, 5 times the weight of the carrier is added with water and mixed evenly, and a nitrate mixed solution of copper nitrate, zinc nitrate, magnesium nitrate and cerium nitrate is prepared with water 15 times the weight of the carrier, the concentrations of which are 1.72 mol / L, 1.15 mol / L, 0.048 mol / L and 0.046 mol / L, respectively, and then the nitrate mixed solution is mixed evenly with the suspension of the carrier and the carbon nanotubes;

[0118] (3) preparing a sodium carbonate solution with 3 times the weight of water of the mixed solution in step (2), wherein the concentration of the sodium carbonate solution is 1.0 mol / L, and then co-precipitating the prepared sodium carbonate solution with the mixed solution in step (2), stirring vigorously during mixing, controlling the pH of the mixed solution to 8.5 and the temperature to 80° C., and aging the mixed solution for 12 h after heat preservation;

[0119] (4) Filter the aged suspension in step (3), and wash the filter cake with deionized water until Na + The concentration is less than 0.1% (calculated as sodium oxide);

[0120] (5) adding 0.1 mol / L potassium hydroxide salt solution at a concentration of 10% by weight of the filter cake to the filter cake in step (4) and mixing well, drying the filter cake at 130° C. for 8 h, drying at 380° C. for 4 h, and then pressing the filter cake into a Φ5*5 mm shaped catalyst;

[0121] (6) The prepared methanol synthesis catalyst was subjected to component analysis and specific surface analysis, and then subjected to 5MPa, 230℃, 10000h -1 Performance evaluation was performed under airspeed conditions.

[0122] Comparative Example 1

[0123] (1) In this method, a sodium aluminate solution with a concentration of 2 mol / L is uniformly mixed with a 2-fold volume of a nitrate mixed solution, wherein the concentrations of copper nitrate, zinc nitrate, magnesium nitrate, chromium nitrate and cerium nitrate in the nitrate mixed solution are 2.15 mol / L, 0.92 mol / L, 0.13 mol / L, 0.023 mol / L and 0.037 mol / L, respectively, and 20-fold water is added for dilution;

[0124] (2) adding carbon nanotubes to the solution of step (1), wherein the weight ratio of carbon nanotubes to alumina in the solution is 1:30, and suspending the carbon nanotubes in the solution and mixing them uniformly;

[0125] (3) preparing a sodium carbonate solution with 3 times the weight of water of the mixed solution in step (2), wherein the concentration of the sodium carbonate solution is 1.1 mol / L, and then co-precipitating the prepared sodium carbonate solution with the mixed solution in step (2), stirring vigorously during mixing, controlling the pH of the mixed solution to 8.5 and the temperature to 80° C., and aging the mixed solution for 10 h after heat preservation;

[0126] (4) Filter the aged suspension in step (3), and wash the filter cake with deionized water until Na + The concentration is less than 0.1% (calculated as sodium oxide);

[0127] (5) adding 0.1 mol / L potassium hydroxide salt solution at a concentration of 10% by weight of the filter cake to the filter cake in step (4) and mixing well, drying the filter cake at 130° C. for 8 h, drying at 380° C. for 4 h, and then pressing the filter cake into a Φ5*5 mm shaped catalyst;

[0128] (6) The prepared methanol synthesis catalyst was subjected to component analysis and specific surface analysis, and then subjected to 5MPa, 230℃, 10000h -1 Performance evaluation was performed under airspeed conditions.

[0129] Comparative Example 2

[0130] This embodiment discloses a method for preparing a methanol synthesis catalyst with an ultra-large specific surface area, comprising the following steps:

[0131] (1) This method uses a specific surface area of ​​360m 2 / g silica gel was used as a carrier, and it was supersaturated with 1.5 mol / L zirconium nitrate solution of 5 times its weight at 80°C, and then heated at 400°C.

[0132] Bake for 10 hours, repeat soaking and drying once more, and use it as a catalyst carrier;

[0133] (2) The carrier and the carbon nanotubes are suspended in water, the weight ratio of the carrier to the carbon nanotubes is 30:1, 5 times the weight of the carrier is added with water and mixed evenly, 20 times the weight of the carrier is used to prepare a nitrate mixed solution of copper nitrate, zinc nitrate and magnesium nitrate, the concentrations of which are 2.5 mol / L, 0.5 mol / L and 0.067 mol / L respectively, and then the nitrate mixed solution is mixed evenly with the suspension of the carrier and the carbon nanotubes;

[0134] (3) preparing a sodium carbonate solution with 3 times the weight of water of the mixed solution in step (2), wherein the concentration of the sodium carbonate solution is 1.0 mol / L, and then co-precipitating the prepared sodium carbonate solution with the mixed solution in step (2), stirring vigorously during mixing, controlling the pH of the mixed solution to 7.4 and the temperature to 85° C., and aging the mixed solution for 10 h after heat preservation;

[0135] (4) Filter the aged suspension in step (3), and wash the filter cake with deionized water until Na + The concentration is less than 0.1% (calculated as sodium oxide);

[0136] (5) adding 0.08 mol / L potassium hydroxide salt solution at a concentration of 15% by weight of the filter cake to the filter cake in step (4) and mixing well, drying the filter cake at 130° C. for 8 h, drying at 380° C. for 4 h, and then pressing the filter cake into a Φ5*5 mm shaped catalyst;

[0137] (6) The prepared methanol synthesis catalyst was subjected to component analysis and specific surface analysis, and then subjected to 5MPa, 230℃, 10000h -1 Performance evaluation was performed under airspeed conditions.

[0138] Comparative Example 3

[0139] This embodiment discloses a method for preparing a methanol synthesis catalyst with an ultra-large specific surface area, comprising the following steps:

[0140] (1) This method uses a specific surface area of ​​360m 2 / g silica gel was used as a carrier, and it was supersaturated with 1.5 mol / L zirconium nitrate solution of 5 times its weight at 80°C, and then heated at 400°C.

[0141] Bake for 10 hours, repeat soaking and drying once more, and use it as a catalyst carrier;

[0142] (2) The carrier and activated carbon are suspended in water, the weight ratio of the carrier to the activated carbon is 30:1, 5 times the weight of water of the carrier is added and mixed evenly, and a nitrate mixed solution of copper nitrate, zinc nitrate, magnesium nitrate and cerium nitrate is prepared with water 20 times the weight of the carrier, with concentrations of 2.5 mol / L, 0.5 mol / L, 0.067 mol / L and 0.025 mol / L, respectively, and then the nitrate mixed solution is mixed evenly with the suspension of the carrier and carbon nanotubes;

[0143] (3) preparing a sodium carbonate solution with 3 times the weight of water of the mixed solution in step (2), wherein the concentration of the sodium carbonate solution is 1.0 mol / L, and then co-precipitating the prepared sodium carbonate solution with the mixed solution in step (2), stirring vigorously during mixing, controlling the pH of the mixed solution to 7.4 and the temperature to 85° C., and aging the mixed solution for 10 h after heat preservation;

[0144] (4) Filter the aged suspension in step (3), and wash the filter cake with deionized water until Na + The concentration is less than 0.1% (calculated as sodium oxide);

[0145] (5) adding 0.08 mol / L potassium hydroxide salt solution at a concentration of 15% by weight of the filter cake to the filter cake in step (4) and mixing well, drying the filter cake at 130° C. for 8 h, drying at 380° C. for 4 h, and then pressing the filter cake into a Φ5*5 mm shaped catalyst;

[0146] (6) The prepared methanol synthesis catalyst was subjected to component analysis and specific surface analysis, and then subjected to 5MPa, 230℃, 10000h -1 Performance evaluation was performed under airspeed conditions.

[0147] Examples 2 to 10 were prepared using similar operations. The ratio of the components in the catalyst was adjusted by changing the concentration of the nitrate solution and the drying conditions. The prepared catalysts were subjected to various analyses and performance evaluations. The analysis data of the samples prepared in 10 groups of examples are shown in Tables 1 and 2, and the analysis data of the other three comparative catalysts are shown in Tables 3 and 4.

[0148] Table 1 Main components and properties of methanol synthesis catalysts prepared in ten examples

[0149]

[0150] Table 2 Specific surface area and activity of methanol synthesis catalysts of ten examples

[0151]

[0152] Table 3 Main components of methanol synthesis catalysts of three comparative examples

[0153]

[0154] Table 4 Specific surface area and activity of methanol synthesis catalysts of three comparative examples

[0155]

[0156] As can be seen from Tables 1 to 4, in Comparative Example 1, silica gel with a large specific surface area was not used as a carrier, and the specific surface area of ​​the final catalyst was much lower than that of Examples 1 to 10. In Comparative Example 2, no rare earth nitrate was added, and the initial activity of the catalyst was relatively poor. In Comparative Example 3, activated carbon with carbon nanotubes was used, and the initial activity of the catalyst was relatively poor.

[0157] The above are the implementation methods listed in this embodiment, but this embodiment is not limited to the above optional implementation methods. Those skilled in the art can arbitrarily combine the above methods to obtain other various implementation methods. Anyone can derive other various forms of implementation methods under the inspiration of this embodiment. The above specific implementation methods should not be understood as limiting the scope of protection of this embodiment. The scope of protection of this embodiment shall be based on the definition in the claims, and the description can be used to interpret the claims.

Claims

1. A method for preparing a methanol synthesis catalyst with an ultra-large specific surface area, characterized in that: The following steps are involved: S1. Silica gel is used as a carrier, and modified silica gel carrier is obtained after modification; S2. The modified silica gel carrier and the carbon nanotubes are dispersed in a solution, and then a nitrate mixed solution is added to the suspension; S3. Then, sodium carbonate solution was added, and the active component was precipitated by co-precipitation and adsorbed on the carrier, and after co-precipitation, the mixture was aged at a constant temperature; S4. The aged suspension was filtered and the filter cake was washed with deionized water to remove the Na + , control the sodium oxide content ≤ 0.10%; S5. The filter cake in step (4) is modified, dried, calcined, and then pressed into tablets to the required size.

2. The method for preparing a methanol synthesis catalyst with an ultra-large specific surface area according to claim 1, characterized in that: The silica gel has a specific surface area of ​​≥350m 2 / g, pore diameter is 3-10nm, and pore volume is ≥0.50ml / g.

3. The method for preparing a methanol synthesis catalyst with an ultra-large specific surface area according to claim 1, characterized in that: The modified silica gel carrier modification method comprises the following steps: immersing the silica gel carrier in a 0.15-1.5 mol / L zirconium nitrate solution at a temperature below 80° C., and then drying the silica gel carrier at a temperature of 260-450° C. for 2-12 hours. The zirconium nitrate in the zirconium nitrate solution is adsorbed on the silica gel surface in the form of zirconium oxide.

4. The method for preparing a methanol synthesis catalyst with an ultra-large specific surface area according to claim 3, characterized in that: The weight ratio of silica gel to zirconium oxide in the modified silica gel carrier is 1:0.08-0.

65.

5. The method for preparing a methanol synthesis catalyst with an ultra-large specific surface area according to claim 1, characterized in that: The weight ratio of the modified silica gel carrier to the carbon nanotubes is 15 to 35:

1.

6. The method for preparing a methanol synthesis catalyst with an ultra-large specific surface area according to claim 1, characterized in that: The nitrate mixed solution comprises zinc nitrate, copper nitrate, magnesium nitrate and rare earth nitrate, and the weight ratio of the carrier before modification to the nitrate mixed solution is 1:10-30.

7. The method for preparing a methanol synthesis catalyst having an ultra-large specific surface area according to claim 6, characterized in that: The concentration of copper nitrate is 0.5-3 mol / L, the concentration of zinc nitrate is 0.2-1.5 mol / L, the concentration of rare earth nitrate is 0.001-0.01 mol / L, and the concentration of magnesium nitrate is 0.5-2 mol / L.

8. The method for preparing a methanol synthesis catalyst with an ultra-large specific surface area according to claim 6, characterized in that: The rare earth element in the rare earth nitrate is Lu, La, Ce or Y.

9. A methanol synthesis catalyst with an ultra-large specific surface area, characterized in that: The composition includes, by weight percentage, 8-20% silicon oxide, 1-9% zirconium oxide, 35-65% copper oxide, 12-30% zinc oxide, 0.5-3% rare earth oxide, 0.01-0.3% potassium oxide and 0.2-3% magnesium oxide.

10. The ultra-large specific surface area methanol synthesis catalyst according to claim 9, characterized in that: The catalyst is prepared by the method for preparing a methanol synthesis catalyst with an ultra-large specific surface area as described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Catalyst for preparing methyl alcohol by catalytic hydrogenation on assistant modified carbon dioxide and preparation method thereof

    CN101983765A

  • Catalyst for preparing methyl alcohol by carbon dioxide catalytic hydrogenation and preparing method thereof

    CN102000578A

  • Novel auxiliary-modified catalyst for preparing methanol by catalytic hydrogenation of carbon dioxide and preparation method of catalyst

    CN102302934A

  • Auxiliary agent-modified catalyst for CO-CO2 co-hydrogenation synthesis of methanol

    CN102716749A

  • Preparation method of copper-based hydrogenation catalyst without reduction activation

    CN104275185A